On the distribution and ecology of Culiseta (Culicella) ochroptera (Peus) (Diptera: Culicidae) in Germany - Kuhlisch, Cornelius; Kampen, Helge; Werner, Doreen (Zootaxa, 2019)
Culiseta ochroptera is a rare mosquito species in Germany, for which little ecological data are available. It is a species of peatlands where it occurs in a variety of habitats in different mire types. These landscape elements, strongly reduced and degraded by human use, are now often protected areas. Within the scope of a Germany-wide mosquito monitoring program, Cs. ochroptera was documented several times from 2011 to 2017, complementing historical data about its distribution and ecology. The records in northern and eastern Germany represent different types of peatlands and aquatic sites. Highest seasonal population densities were recorded in July and August, caused by the second of at least two annual generations. The morphological variants of Cs. ochroptera as described in the past were assigned to three forms (light, normal, dark), and the previously noted but neglected presence of postspiracular scales is recognized as a useful character supporting species identification.